Pendampingan Branding Produk Dengan Menggunakan Aplikasi Canva Pada LKP Khiara Training Centre - Idham; Imam Dinata, Muhammad (Pendidikan Matematika, FKIP Universitas Mataram, 2023)
The utilization of digital technology in the era of Industry 4.0 provides significant benefits, especially in the tourism and culinary sectors. Digital branding, which creates product identity through technology, is crucial in promoting products and creating a positive perception in society. Training institutions such as Khiara Training Center play a role in imparting skills to the community. The use of digital marketing by small and medium-sized enterprises (SMEs) can expand their marketing reach nationally and internationally. Graphic design, including infographic design, involves arranging graphic elements for effective visual communication. The Canva application, a drag-and-drop-based design tool, is an effective solution for product branding and graphic design. The implementation methods of the outreach activities involve monologous methods for content delivery and dialogic methods through discussions. The preparation phase includes problem understanding, collecting reference materials, and scheduling. The execution phase involves a two-day training, with the presentation of Canva's features on the first day and hands-on practice on the second day. Evaluation and final reporting are used to assess participants' understanding and the outcomes of the activities. This initiative successfully trained 20 participants from various educational backgrounds in using the Canva application for product branding design